Human resources development model of Indonesian National Police: Case study in Lamongan Resort Police - Dhirotsaha, Widyagana Putra; Suhariadi, Fendy; Wijoyo, Suparto (Technium Social Sciences Journal, 2026)
This study aimed to identify and analyze the current Indonesian National Police human resource development model at the Lamongan Police Resort and implemented efforts to realized more precise and transparent human resource development in Indonesian National Police. This type of research used a qualitative approach with a single case study design. Data collection techniques were done by interviewing, observing, and reviewing documents. This study used a purposive informant selection technique to selected 10 informants. Data analysis in this study used data reduction, data presentation, conclusion, and verification with data validity tests. The results of the study indicated that: 1.) Improving the human resource development strategy of the Indonesian National Police adapting the era of the Industrial Revolution 4.0 towards the era of policing 5.0; 2.) Big Data Development; 3.) Recruitment to obtain superior quality human resources; 4.) Indonesian National Police Talent Management; 5.) Performance Management; 6.) Increasing capabilities based on technology; 7.) Job design by the Grand Strategy of the Indonesian National Police 2025-2045. On the other hand, there were series of efforts made by the Institution of Indonesian National Police in developing optimally integrated human resources to be precise and transparent, namely: 1.) The need for Indonesian National Police personnel who have qualities such as special competencies; 2.) Handling the emergence of new crimes; 3.) Modernization and Digitalization of Public Services; 4.) Up-skilling and up-reskilling to build a perfect Indonesian National Police (world-class organization).